Digital payments in firm networks: Theory of adoption and quantum algorithm - Sofia Priazhkina; Samuel Palmer; Pablo Martín-Ramiro; Román Orús; Samuel Mugel; Vladimir Skavysh (Bank of Canada, 2024)
We build a network formation game of firms with trade flows to study the adoption and usage of a new digital currency as an alternative to correspondent banking. We document endogenous heterogeneity and inefficiency in adoption outcomes and explain why higher usage may correspond to lower adoption. Next, we frame the model as a quadratic unconstrained binary optimization (QUBO) problem and apply it to data. Method-wise, QUBO presents an extension to the potential function approach and makes broadly defined network games applicable and empirically feasible, as we demonstrate with a quantum computer.
Keywords: C6; C71; D4; D85; G; L22; 330; Central bank research; Digital currencies and fintech; Digitalization; Economic models; Financial institutions; Payment clearing and settlement systems; Sectoral balance sheet